Espirito Santo: a industrialização como fator de desautonomia relativa - Medeiros, Antonio Carlos de (1977)
This paper is on one hand an analysis of historical and dialectical conditions which explain the comparatively economic backwardness of the State of Espírito Santo as a peripheral underdeveloped region, and on the other hand a study of thc far-reaching consequences of the implementation in its territory of the so-called ~npact p~oje~, and from the standpoint of pol icy-making, of the steps to be taken in order to integratc Espírito Santo into national economic context Since the changing process in our State is traceable to the development of the Occidental Center, stress is laid upon the transformations through which the Great Capital ist Center has been formed, and consequently the coming into being of the National State. An attempt is made to give a bird's-eye-view of the whole history of capitalism and the evolution from capitalism itself toward 1 iberal democracy, economicliberalism, political pluralism and the oligopolistic economic structure. It is also shown that such an evolution has been partly due to the intervention of the then authoritarian state abetted by the Old Republ ic liberal tendencies. The conclusion is drawn that the caracteristic feature of Br~zil ian Capital ism was accounted for by the early goods exporting phase, and that Espírito Santo partook of the same conditions, the only difference beillg the time-lag as regards the national and inter~ational centers. Thus the economic growth of Espírito Santo has always depended upon the development of the other inter and intraregional centers, and the a~thor tries to inquiry into the pecul iarities that characterizes such a region, by dividing it into four phases. First of alI, there was a subsistence stage, followed by a cycle of exportation of raw-materials, which is explained to some extent by its geographical conditions. Such caracteristics have shaped the occupation of its territory, explaining its rhythm and degradation. AlI the changing process is unleashed from the moment in which the Great Projects began tó operate new and unpredictable changes, in function of the six bill ion doI lar investments appl ied in a state the budget of which can hardly cover its personnel expenditures. It should not be lost sight of that the implementation of such Great Projects will strengthen the potential influence of Federal Government, and this will contribute to the putting aside of the local public authorities as well as to the weakening of privately owned firms d~cision-making to the detriment of Espírito Santo autonomy, which is herein called: pno netativ~ lo autonomy. Thus particular emphasis is laid upon the transformation attendant upon the impJementation of such projects and upon the risks there are to be feared. The fast increase in the State internaI income, the concentration of such income in terms of space and social strata, the excessive demographic boom around the metropolitan area and the bringing into existence of several satel lite and complementary industries have been taken into due account.